Analisis stilistika antologi puisi Li Bai dan Sudi Yatmana: Teori Northrop Frye - Widuri, Ananda Wahyu Puspa; Khoir, Syihabul; Darni, Darni; Yunita, Vira; Li, Sijie (Universitas Mulawarman, 2024)
The aim of this research is to analyze the stylistic elements and imagery in the poems of Li Bai and Sudi Yatmana using Northrop Frye's theory, and to understand how these elements convey meaning and nuance in their works. The research employs a stylistic approach with a descriptive-qualitative design. Data were collected from offline sources (books, notes, archives) and online sources (digital), categorized into primary data (poems by Li Bai) and secondary data (books by Sudi Yatmana). The findings indicate that Li Bai's poems, such as 静夜思 Jìngyè sī, 月下独酌 Yuè xià dúzhuó, and 早发帝城 Zǎo fā bái dì chéng, use poetic language rich in personification and metaphor to depict deep feelings towards nature and philosophical contemplation. In contrast, Sudi Yatmana's poems, such as Paman Tani Jawa Purwa, Nandur Pari Jero, and Panen, are more realistic, portraying the everyday lives of farmers with vivid details and a profound appreciation for the human-nature relationship. This analysis demonstrates that Li Bai's works exude romanticism and introspection, while Yatmana's poems highlight the cultural richness and agricultural life of rural Java.